Оленеводство в бассейне р. Тром-Аган: история и современность - Isaeva, T. A.; Исаева, Т. А. (Издательство Тюменского государственного университета, 2016)
The basin of Trom-Agan historically has the most number of reindeer among all areas of the Surgut district. In the pre-Soviet period the reindeer breedinghad transport direction. Attempts to redirect this branch of farming into commodity base were made during the time of collectivization in the USSR. For achieving this goal tundra grazing techniques were supposed to be use. However, reindeer collective farms have been consistently unprofitable due to inefficiency of the new methods in conditions of taiga. Since the beginning of the industrial development of Surgut district territories interest in native collective farms steadily declined. However, up to 1970-ies. transport reindeer remained and it depended on local industry enterprises. In the late 1980-ies. collective farms were dismissed and livestock became private. Since the beginning of the 1990-s. an intensive growth of personal herds with an improved forms of maintenance was noted, reindeer husbandry has turned into commodity form. In our days Trom-Agan remains the leading reindeer area, not only of the Surgut district, but generally of Ugra as well. Рассматриваются история и современность тундрового оленеводства бассейна р. Тром-Аган.